2011
DOI: 10.4103/0970-0218.84130
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome of women with gestational diabetes in a tertiary level hospital of North India

Abstract: Background:Women with gestational diabetes mellitus (GDM) pose an important public health problem because diabetes not only affects the maternal and fetal outcome, but these women and their fetuses are also at an increased risk of developing diabetes and related complications later in their life.Objectives:The study was conducted to determine the maternal and fetal outcomes of 50 diabetic vs 50 normoglycemic pregnancies.Materials and Methods:This was a retrospective analytical record-based study conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
48
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 9 publications
11
48
4
1
Order By: Relevance
“…6% babies were intrauterine deaths in the present study similar to 6% intrauterine deaths reported in the study by Saxena et al 10 The Indian consensus is that a new born weighing >3.5 kg should be considered as macrosomia. In present study, 40% babies were macrosomic at birth which is high compared to other Indian studies were the incidence was 28%.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…6% babies were intrauterine deaths in the present study similar to 6% intrauterine deaths reported in the study by Saxena et al 10 The Indian consensus is that a new born weighing >3.5 kg should be considered as macrosomia. In present study, 40% babies were macrosomic at birth which is high compared to other Indian studies were the incidence was 28%.…”
supporting
confidence: 90%
“…According to Shefali et al, 1.4% babies had congenital anomalies, while according to Saxena et al, 10% babies had congenital anomalies. 4,10 In present study 37 patients followed up at 6 weeks with FBS and PLBS. Out of these, 16.2% patients were found to have diabetes on follow-up.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The incidence of pregnancy-induced hypertension (PIH); hypothyroidism and polyhydramnios were also observed more in diabetic pregnancies. 13 Good glycemic control is mandatory and it can be done by diet, exercise with or without insulin. Ultrasonography of pregnancy profile, anomaly scan as well as foetal echocardiography plays a very important role in this type of high risk pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, caesarian section rate was 74% which is higher compared to the findings of Jensen DM et al, Bener AB et al and Saxena P et al, who observed CS rate as 33%, 27.9%, 42% respectively. [16][17][18] The main indications for CS being previous caesarian, cephalopelvic disproportion, fetal distress, malpresentation and fetal macrosomic. The present study showed 9% of perinatal deaths in GDM compared to 1% deaths in control group.…”
Section: Resultsmentioning
confidence: 99%